До 85 річчя академіка А. Ф. Попова - katalizadmin, katalizadmin (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2022)
To the 85th birthday of Academician A. F. Popov